EVALUATION OF SOUTH SULAWESI ON STUDENT DEVELOPMENT AND TRAINING PROGRAM - Hasyim altaf; Herman Herman (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2017)
AbstracThe purpose of this study is to provide reports on the advantages, weaknesses and recommendations related to the program to become better at PPLP in South Sulawesi in terms of context, input, process and product (CIPP) with qualitative and quantitative research approach. The instrument of this research is observation, documentation and questionnaire arranged to collect quantitative data, while interview guidance instrument is arranged to collect qualitative data. The data collected from the elements of trainers, athletes, and administrators were analyzed quantitatively descriptive percentage using microsoft excell and qualitative data analysis triangulation. The result of South Sulawesi PPLP evaluation is statistically from context variable, input, process, product as a whole has been done well with 70.30% percentage. The evaluation of context variables shows excellent results with a 90% percentage. The input evaluation showed good results with the percentage of 61.40%. The results of the evaluation process showed good results with a percentage of 77.46%. Product evaluation results show considerable results with 52.34% percentage.Keywords: Program Evaluation, CIPP, PPLP Coaching South Sulawesi.